PENGGUNAAN BIJI PLASTIK LOW DENSITY POLYETHYLENE (LDPE) PADA CAMPURAN BERASPAL AC - BASE - Febiansyah Azhar; Rinto Permana; Linda Aisyah; Ardianto Tri Pradityo (Direktorat Bina Teknik Jalan dan Jembatan, 2025)
Roads are one of the key infrastructures supporting public mobility. However, road conditions in Indonesia still face various issues, one of which is the frequent occurrence of road damage even before reaching the planned service life. This damage is generally caused by the insufficient stability of asphalt mixtures, which prevents pavement layers from optimally withstanding traffic loads. One type of asphalt mixture that can address this issue is AC-Base, which functions as a supporting layer beneath the surface layer and transfers traffic loads to the subgrade. Therefore, additive materials are needed to improve the stability and durability of the AC-Base mixture. One of the additives used in this study is LDPE plastic pellets, as previous research has shown that LDPE can improve the properties of asphalt mixtures, particularly stability. However, further research is required regarding the use of LDPE plastic pellets to acknowledge the effect of the use of Low-Density Polyethylene (LDPE) plastic pellets on the characteristics of an AC-Base mixture, and to obtain the LDPE optimum content with various content levels, namely 2%, 4%, 6%, and 8% by weight of asphalt. Based on the experimental results, the LDPE plastic pellet content that met the specified criteria was 2%. The comparison between the control AC-Base mixture and the modified AC-Base mixture with 2% LDPE pellets and AC-Base mixture modified with LDPE plastic pellets on the optimum content of asphalt at 4,5% showed an increase in density from 2.33 gr/cm³ to 2.35 gr/cm³ and residual stability from 90.24% to 91.08%. However, several other parameters decreased slightly: VIM from 3.18% to 3.16%, VMA from 14.13% to 13.56%, VFB from 83.49% to 82.15%, and stability from 1856.33 kg to 1839.34 kg. This research contributes to the development of more sustainable pavement material by utilising polymer waste for asphalt mixture engineering. Kata Kunci: AC-Base, Plastik LDPE, Stabilitas, Volumetrik Aspal, Kadar Optimum Plastik LDPE Keywords: AC – Base, LDPE Plastic, Stability, Asphalt Volumetric, Optimum LDPE Plastic Content